Modelling energy utilization for laying type Pullets - Neme, R [UNESP]; Sakomura, NK [UNESP]; Fialho, FB; Freitas, ER [UNESP]; Fukayama, EH [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2005)
Three trials were carried out to determine energy metabolized (EM) requirement model for starting and growing pullets from different strains, at five ambient temperatures and different percentage feather coverage. In Trial I, metabolizable energy requirements for maintenance (MEm) and efficiency of energy utilization were estimated using 64 birds of two different strains, Hy-Line W36 (HLW36) and Hy-Line Semi-heavy (HLSH), from 9 to 13 weeks of age. The effects of ambient temperature (12, 18, 24, 30 and 36ºC) and percentage feather coverage (0, 50 and 100%) on MEm were assessed in the second trial, using 48 birds per temperature per strain (HLSH and HLW36) from 9 to 13 weeks of age. Trial III evaluated ME requirements for weight gain (MEg) using 1,200 birds from two light strains (HLW36 and Hisex Light, HL) and two semi-heavy strains (HLSH and Hisex Semi-heavy, HSH) reared until 18 weeks of age. According to the prediction models, MEm changed as a function of temperature and feather coverage, whereas MEg changed as a function of age and bird strain. Thus, two models were developed for birds aged 1 to 6 weeks, one model for the light strain and one for the semi-heavy strain. Energy requirements (ER) were different among strains from 7 to 12 weeks, and therefore 4 models were elaborated. From 13 to 18 weeks, one single model was produced for semi-heavy birds, since ER between semi-heavy strains were not different, whereas two different models were elaborated for the light layers. MEg of light birds was higher than MEg of semi-heavy birds, independent of age.
Keywords: Body composition; energy requirements; feather coverage; Laying hens; model; Temperature